WHAT TIME DOES IN LANGUAGE: A CROSS-LINGUISTIC COGNITIVE STUDY OF SOURCE RELATED VARIATION IN VERBAL TIME METAPHORS IN AMERICAN ENGLISH, FINNISH AND HUNGARIAN - MÁTHÉ, Zsuzsa (Studia Universitatis Babeș-Bolyai Philologia, 2021)
What Time Does in Language: a Cross-Linguistic Cognitive Study of Source Related Variation in Verbal Time Metaphors in American English, Finnish and Hungarian. Such a universal yet abstract concept as time shows variation in metaphorical language. This research focuses on metaphorical language within the framework of the cognitive metaphor theory, investigating time through a contrastive cross-linguistic approach in three satellite-framed languages. By combining qualitative and quantitative methods, this study attempts to identify what time does in language in a metaphorical context, with a focus on verbs in causative constructions (e.g. time heals) as well as manner of motion verbs (e.g. time rushes), through an empirical corpus-based study complemented by the lexical approach. The two main conceptual metaphors that are investigated in this study are time is a changer and time is a moving entity. While these two conceptual metaphors are expected to be frequent in all three languages, differences such as negative/positive asymmetry or preference of a type of motion over another are expected to be found. The primary objective is to explore such differences and see how they manifest and why. The hypothesis is that variations among the three languages related to the source domain (changer and moving entity), are more likely to be internal and not external. The purpose is to investigate these variations and to determine what cognitive underpinnings they can be traced back to, with a focus on image schemas. The study reveals that source internal variation does prevail over source external variation. The results show that cross-linguistic differences of such a relevant concept as time do exist but more often through unique characteristics of the same source domain rather than new, distinctive domains. REZUMAT. Ce face timpul: un studiu cognitiv al variațiilor conceptuale legate de domeniul sursă în metafora timpului în engleză americană, finlandeză și maghiară. Un concept atât de universal, dar abstract, precum timpul, prezintă variații în limbajul metaforic. Această cercetare se concentrează pe limbajul metaforic în contextul teoriei metaforei conceptuale, investigând imaginea timpului printr-o analiză contrastivă în trei limbi satelitare. Prin combinarea metodelor calitative și cantitative, acest studiu identifică ce face timpul într-un context metaforic, cu accent pe verbe în construcții cauzale (timpul vindecă), precum și verbe de mișcare (timpul fuge), printr-un studiu empiric bazat pe corpus completat de abordarea lexicală. Cele două metafore conceptuale principale care sunt investigate în acest studiu sunt timpul este un agent schimbător și timpul este o entitate în mișcare. Se anticipează că rezultatele studiului vor arăta faptul că, deși cele două metafore conceptuale sunt frecvente în toate cele trei limbi, există anumite diferențe, precum asimetria între imaginea negativă/pozitivă a timpului sau preferința pentru un tip de mișcare față de altul. Obiectivul principal este de a explora diferențele de acest fel și de a vedea cum se manifestă și de ce. Ipoteza este că variațiile dintre cele trei limbi legate de domeniul sursă (agent schimbător și entitate în mișcare) sunt mai degrabă interne și nu externe. Scopul este de a investiga aceste variații și de a determina pe ce principii cognitive sunt bazate, cu accent pe schemele imagistice. Studiul dezvăluie faptul că variațiile interne ale sursei domeniu prevalează asupra variațiilor externe. Rezultatele arată că există diferențe inter-lingvistice ale unui concept atât de relevant precum timpul, dar aceste diferențe se manifestă mai degrabă prin caracteristici unice ale aceluiași domeniu sursă decât prin domenii noi distincte. Cuvinte-cheie: lingvistică cognitivă, teoria metaforei conceptuale, corpus, implicaţii metaforice, domeniul sursă